2020
DOI: 10.1016/j.jbmt.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a biotensegrity focused therapy for the treatment of pelvic organ prolapse: A retrospective case series

Abstract: Introduction: Pelvic organ prolapse (POP), the bulging of pelvic organs into the vagina, is a common condition thought to be caused by weak pelvic tissue. There is a paucity of evidence supporting current treatment approaches. This case series proposes a new biotensegrity-focused hypothesis that POP is caused by taut pelvic tissue and that releasing pelvic tension will improve POP. Methods: Three retrospective patient cohorts are presented illustrating the development of the new biotensegrity-focused therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Some suggest TrPs are present in up to 85% of individuals with colorectal, urological and gynecological pelvic pain syndromes, and can be responsible for many of the symptoms related to these syndromes [ 43 ]. It was suggested that TrPs or myofascial tension, not exerted by external forces, can apply enough force to cause various abnormalities, including compression and entrapment of anatomical structures [ 44 ], decrease joint range of movement [ 7 , 16 ], affect visceral organs [ 9 , 45 , 46 ], lead to musculoskeletal abnormalities [ 47 ], and alter blood and lymph flow [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some suggest TrPs are present in up to 85% of individuals with colorectal, urological and gynecological pelvic pain syndromes, and can be responsible for many of the symptoms related to these syndromes [ 43 ]. It was suggested that TrPs or myofascial tension, not exerted by external forces, can apply enough force to cause various abnormalities, including compression and entrapment of anatomical structures [ 44 ], decrease joint range of movement [ 7 , 16 ], affect visceral organs [ 9 , 45 , 46 ], lead to musculoskeletal abnormalities [ 47 ], and alter blood and lymph flow [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 Some suggest TrPs are present in up to 85% of individuals with colorectal, urological and gynecological pelvic pain syndromes, and can be responsible for many of the symptoms related to these syndromes. 43 It was suggested that TrPs or myofascial tension, not exerted by external forces, can apply enough force to cause various abnormalities, including compression and entrapment of anatomical structures, 44 decrease joint range of movement, 7,16 influence viscera, 9,45,46 lead to musculoskeletal abnormalities, 47 and alter blood and lymph flow. 48…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research investigations on biotensegrity based biomechanical models, particularly cellular, molecular, organ and tissue, organisms and fascial biotensegrity, as well as the principle of biotensegrity in cellular mechanical signal transduction (mechanotransduction), were reported [1,2]. To date, biotensegrity as a model emulated from the forms and functions of complex biological systems has been suggested for several potential applications such as in medical technology [3], health care practices [4] and engineering applications [5].…”
Section: Introductionmentioning
confidence: 99%